IMPACT OF FINANCIAL LITERACY ON INVESTMENT BEHAVIOR OF YOUNG INVESTORS IN INDIA: AN EMPIRICAL STUDY (IITM Journal of Business Studies, 2024)
Financial literacy and knowledge lead to  perceived financial understanding. These  contribute to the decision-making for savings  and investments. Such literacy is a function  of awareness, experience, and skills. Financial  literacy forms a positive financial attitude  towards the achievement of financial goals and  freedom. The level of financial literacy of an  individual makes them more rational in making  their financial decisions. Having good financial  knowledge and understanding would help in  the management of their finances and further  planning of their money in a better way. This  study is descriptive in nature. In this study, a  structured questionnaire was used to measure the  financial literacy of the young investors ranging  between the ages of 18 to 35. The sample size of  the study is 390. The data were collected with  the help of a structured questionnaire. With  the help of “Exploratory Factor Analysis” and  “Multiple Regression Analysis,” it was found  that there is a significant impact of Financial  Literacy (Financial Behavior, Financial Attitude,  Financial Knowledge-Basic, and Financial  Knowledge-Advanced) on the investment  behavior of young investors in India.
Keywords: Financial literacy; financial attitude; financial knowledge; investment behavior; young investors